PENGARUH KEPEMILIKAN INSTITUSIONAL, PROFITABILITAS, DAN KOMITE AUDIT TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BEI 2022-2024 - Hasanah, Aswatun; Khamimah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the effect of institutional ownership, profitability, and audit committee on firm value in banking companies listed on the Indonesia Stock Exchange (IDX) during the period 2022–2024. Firm value is an important indicator used to evaluate a company's success in increasing shareholders’ wealth and reflects investors’ perceptions of the company’s performance and future prospects. In the banking sector, firm value is not only influenced by financial performance but also by the implementation of good corporate governance mechanisms. This research employs a quantitative approach using panel data regression analysis. The research sample consists of 40 banking companies selected through purposive sampling, resulting in a total of 120 observations during the three-year research period. The data used in this study are secondary data obtained from annual reports and financial statements published by the companies on the Indonesia Stock Exchange. The results show that institutional ownership, profitability, and the audit committee simultaneously have a significant effect on firm value. This indicates that both external and internal monitoring mechanisms, along with financial performance, play an important role in increasing firm value in the banking sector. This study is expected to provide insights for investors, company management, and regulators in understanding the factors influencing firm value.